Difference, boundaries and violence : a philosophical exploration informed by critical complexity theory and deconstruction - Hermanus, Lauren (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MA (Philosophy))--University of Stellenbosch, 2010.